The tendency of universalization and unification of law as one of the directions of influence of globalization on national legal system - Хаутова, М. Г. (Theory and practice of jurisprudence, 2016)
One of the tendencies of development of the law in the context of globalization – the tendency to universalize and unification of the law was analyzed in the article. It was determined that the basis of this tendency is an objective process of integration of the world economy, finance, communications, media and other means and spheres of life that could not affect both on the evolution of law in general and on the tendencies of its further development. The main ways (forms) of universalize law were listed and their content was analyzed.